Share Price Analyst With PBV, DER, And EPS At Initial Public Offering - Kriswanto Kriswanto (The Winners, 2016)
Underpricing and overpricing are commonly happened in stocks market. Underpricing happened when IPO pricing was lower than closing price in the first day stock been trade in the market. There were some measurements to be used, like Price to Book Value (PBV), Price Earning Ratio (PER), Earning Per Share (EPS), Debt to Equity Ratio (DER), Net Profit Margin (NPM), Size of Company (Size) and Company Age (Age). The type of research was quantitative with a comparative analysis which focused on the study of literature to support research by describing theories related to the title of the study, data collection of financial statements, and annual reports of companies going public as well as Fact Book published. This article used data from 78 companies that did IPOin 2010 to 2013. This research finds that some statistic used to show majority variables that influence to underpricing is PBV, PER, DER,and Size.